Improved Performance and Stability of All‐Inorganic Perovskite Light‐Emitting Diodes by Antisolvent Vapor Treatment. (15th May 2017) - Wu, Chen; Zou, Yatao; Wu, Tian; Ban, Muyang; Pecunia, Vincenzo; Han, Yujie; Liu, Qipeng; Song, Tao; Duhm, Steffen; Sun, Baoquan
Abstract : All‐inorganic perovskite light‐emitting diodes (LEDs) reveal efficient luminescence with high color purity, but their modest brightness and poor stability are still critical drawbacks. Here, the luminescent efficiency and the stability of perovskite LEDs (PeLEDs) are boosted by antisolvent vapor treatment of CsPbBr3 embedded in a dielectric polymer matrix of polyethylene oxide (PEO). A unique method is developed to obtain high quality CsPbBr3 emitting layers with low defects by controlling their grain sizes. CsPbBr3 in PEO matrix is post‐treated with antisolvent of chloroform (CF), leading to microcrystals with a size of ≈5 µm along the in‐plane direction with active emitting composite of 90%. A device based on CF post‐treatment (CsPbBr3 ‐PEO‐CF) film displays a brightness of up to 51890 cd m −2 with an external quantum efficiency of 4.76%. CsPbBr3 ‐PEO‐CF PeLED still maintains 82% of its initial efficiency after 80 h continuous operation in ambient air, which indicates relatively good device stability. This work highlights that film quality is not only key to promoting fluorescence in CsPbBr3, but also to achieving higher performance PeLEDs. Abstract : Antisolvent vapor treatment of CsPbBr3 films embedded in a dielectric polymer matrix film is proposed, resulting in microcrystal size of ≈5 µm with low defect density. A light‐emitting diode based on composite CsPbBr3 films with this antisolvent vapor treatment displays a brightness of 51890 cd m −2 and an external quantum efficiency of 4.76%.